THE UTILIZATION OF GOOGLE CLASSROOM IN LEARNING ENGLISH - Novia Sagita Maharani (Dialectical Literature and Educational Journal, 2022)
The aims of this research is to observe that (1) the use of Google Classroom during Online Learning during the covid-19 pandemic is very useful in English subjects. (2) Especially in the assignments in class, assessment, and providing material in English subjects in SMPN 6 Bekasi of 7th grade. The method used in this research is descriptive qualitative. to collect the data the researcher used questionnaires, interviews and observations while using the Google Classroom application in the classroom during the application of Online Learning. This research data uses a questionnaire with 10 statements and interviews with 10 questions related to the use of Google Classroom in Learning English through google forms which were distributed to 35 students as respondents. Based on the results obtained by the researcher, that 51.4% strongly agree of 35 students that the Google Classroom application is very useful, easy to use, and very helpful for students in teaching and learning activities during Online Learning in English subjects. The features (Assignment, Assessment, and Provide materials) contained in the Google Classroom application are also very helpful for students based on the highest presentation results in this study, obtained 60% strongly agree from all respondents. Furthermore, the use of the Google Classroom application during the covid-19 pandemic when the application of Online Learning could be utilized by students as a media to support teaching and learning activities in English subjects.